The race to x-ray microbeam and nanobeam science - Ice, Gene E; Budai, John D; Pang, Judy W L (Science (American Association for the Advancement of Science), 2011)
X-ray microbeams are an emerging characterization tool with broad implications for science, ranging from materials structure and dynamics, to geophysics and environmental science, to biophysics and protein crystallography. We describe how submicrometer hard x-ray beams with the ability to penetrate tens to hundreds of micrometers into most materials and with the ability to determine local composition, chemistry, and (crystal) structure can characterize buried sample volumes and small samples in their natural or extreme environments. Beams less than 10 nanometers have already been demonstrated, and the practical limit for hard x-ray beam size, the limit to trace-element sensitivity, and the ultimate limitations associated with near-atomic structure determinations are the subject of ongoing research.